Combination therapeutics in complex diseases. Issue 12 (7th September 2016) - He, Bing; Lu, Cheng; Zheng, Guang; He, Xiaojuan; Wang, Maolin; Chen, Gao; Zhang, Ge; Lu, Aiping
Abstract: The biological redundancies in molecular networks of complex diseases limit the efficacy of many single drug therapies. Combination therapeutics, as a common therapeutic method, involve pharmacological intervention using several drugs that interact with multiple targets in the molecular networks of diseases and may achieve better efficacy and/or less toxicity than monotherapy in practice. The development of combination therapeutics is complicated by several critical issues, including identifying multiple targets, targeting strategies and the drug combination. This review summarizes the current achievements in combination therapeutics, with a particular emphasis on the efforts to develop combination therapeutics for complex diseases.